(3GdLf ai GdMOhJI GdeUQjI (B: s (3OGQSI afjI ddMhGOjJ GdeLehYI ef EMOi bQi UYjO eUQ (B= The jinn in the Egyptian haddutah , A technical study / s - (3CSGeI eMeO YWjIs; (3CMeO Ydi eQSi (B: s; (3NWQi YQGHi (B: s ((3GdbGgQI (B: s (3CSGeI eMeO YWjI (B: s, 2018)
(3JJfGhd gPg GdOQGSI MhGOjJ GdLf h GdOhQ GdhXjai dgPg GdeNdhbGJ GdYLjHI ai GdTcjd Gdafi dJdc GdMhGOjJ h Jdcjd GdKbGaI GdTYHjI(B. (3h Jbhe GdOQGSI Ydi eYGdLI TNUjI GdLf ai GdMhGOjJ GdeUQjI HZjI GdhUhd Edi GdUhQI GdafjI GdJi nqUhQ HgG GdboGUd GdTYHi GdnqLf h Pdc ef NdGd OQGSI JTcjdGJg ai GdMhGOjJ GdeUQjI(B. (3h Jcef CgejI gPg GdOQGSI ai GdRGhjI GdeZGjQI GdJi JfXQ HgG Edi ehVhY TZd HOQGSJI cKjQ ef GdHGMKjf(B: (3ZjQ Cf gPg GdOQGSGJ GdSGHbI cGfJ EeG OQGSGJ hUajI ddeYJbOGJ GdTYHjI Ch QUOG dLGfH hGMO ef LhGfH GdYdGbI Hjf GdLf h GdEfS (B{u(32013(B} (3LGfH GdYTb hGdRhGL(B{u(32013(B} (3ceG UhQJgG GdGTcGd GdCOHjI GdTYHjI GdeNJdaI(B. (3h bO GYJeO GdHGMK ai gPg GdOGQSI Ydi GdMhGOjJ GdJi Je LeYgG h JOhjfgG HeYQaJg ceG SjSJNOe GdHGMK ai gPg GdOQGSI GdefgL GdhUai GdJMdjdi dhUa h JMdjd CHYGO GdXGgQI eMd GdOQGSIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GddZI GdYQHjI h BOGHgG s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCOH GdTYHi s; (3GdLfs; (3GdMhOGjJ s